Optimization of Thin Shell Structures Using FSD Algorithms - Milan Saga; Martin Dudinsky; Peter Pechac (Communications - Scientific letters of the University of Zilina, 2012)
The paper presents a theoretical and numerical study of the efficiency of the fully stress design (FSD) algorithm in the case of thin shell finite elements. Relation between membrane forces, bending moments and the element thickness is analysed by means of numerical tests. Subsequent numerical testing and a new iterative algoritm to providing the rapid convergence of the optimizing process is proposed.